2021
DOI: 10.1177/1759720x21995069
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Cyclin-dependent kinase 7 (CDK7) is an emerging prognostic biomarker and therapeutic target in osteosarcoma

Abstract: Background: Overexpression of cyclin-dependent kinase 7 (CDK7) is a well-known pathogenic feature of various malignancies and a sign of a more dismal prognosis. As relatively little is known about CDK7 in osteosarcoma, we elected to evaluate its expression, prognostic value, and function. Methods: We began by analyzing the publicly available data sets on CDK7 expression, including RNA sequencing data from the Therapeutically Applicable Research to Generate Effective Treatments on Osteosarcoma (TARGET-OS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
“…S2). VitroGel has been previously reported to study various cancer types including pancreatic cancer [58], melanoma [59], breast cancer [60,61], non-small cell lung cancer [62], and osteosarcoma [63]; however, its application in DLBCL investigations is yet to be explored. Though this relatively simple, feasible, and reproducible 3D model led to a more clinically relevant phenotype of DLBCL cells, it lacks the interaction of cancer cells with other cell types comprising tumor microenvironment, such as stromal cells and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing breast cancer TMAs for CDK7 (n = 945), the study found that patients with high-grade and extensive tumors, or those with recurrent disease, exhibited lower CDK7 expression. Elevated CDK7 levels were instead associated Breast cancer [70], Gastric cancer [54], Osteosarcoma [115], Synovial sarcoma [116], Thyroid carcinoma [117], T cell acute lymphoblastic leukemia [118] No [95], Head and neck squamous cell carcinoma [121], Thyroid cancer [122], Neuroblastoma [123], Glioblastoma [124], Gastrointestinal stromal tumours [125], Pancreatic cancer [126], Hepatocellular carcinoma [127], Gallbladder cancer [39], Cholangiocarcinoma [128], Colorectal cancer [40], Nasopharyngeal carcinoma [129], Prostate cancer [130], Renal cell carcinoma [131], Urothelial carcinoma [132], Bladder cancer [133], Melanoma [134], Osteosarcoma [135], lymphomas [62], Leukemia [43] No with extended BCSS and prolonged time to distant metastasis [67]. This landscape of disparate findings illustrates the complexity of CDK7's role within breast cancer prognosis and highlights the necessity for further refined and targeted investigations.…”
Section: The Expression Of Cdk7 and Its Prognostic Value In Breast Ca...mentioning
confidence: 99%